Teaching English Language through Technologies - Ismanqulova Nigora To‘lqin qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
In the last two decades, technology has become an essential component of English language teaching (ELT). Mobile-Assisted Language Learning (MALL), online platforms, interactive multimedia, and artificial intelligence (AI) tools provide new opportunities for flexible, effective, and motivating instruction. This thesis reviews key studies and presents evidence on how digital technologies enhance vocabulary, pronunciation, listening, speaking, and overall proficiency, while also examining challenges, pedagogical recommendations, and future directions. The rise of online education is just one instance of how technological advancements are transforming English Language Teaching. Language learning in the classroom is becoming more digitized as innovative technologies are woven into every facet of teaching, including lesson planning, assessment, and professional development.